CXCL10 Acts as a Bifunctional Antimicrobial Molecule against Bacillus anthracis - Katie R. Margulieux (American Society for Microbiology, 2016)
ABSTRACT Bacillus anthracis is killed by the interferon-inducible, ELR(−) CXC chemokine CXCL10. Previous studies showed that disruption of the gene encoding FtsX, a conserved membrane component of the ATP-binding cassette transporter-like complex FtsE/X, resulted in resistance to CXCL10. FtsX exhibits some sequence similarity to the mammalian CXCL10 receptor, CXCR3, suggesting that the CXCL10 N-terminal region that interacts with CXCR3 may also interact with FtsX. A C-terminal truncated CXCL10 was tested to determine if the FtsX-dependent antimicrobial activity is associated with the CXCR3-interacting N terminus. The truncated CXCL10 exhibited antimicrobial activity against the B. anthracis parent strain but not the ΔftsX mutant, which supports a key role for the CXCL10 N terminus. Mutations in FtsE, the conserved ATP-binding protein of the FtsE/X complex, resulted in resistance to both CXCL10 and truncated CXCL10, indicating that both FtsX and FtsE are important. Higher concentrations of CXCL10 overcame the resistance of the ΔftsX mutant to CXCL10, suggesting an FtsX-independent killing mechanism, likely involving its C-terminal α-helix, which resembles a cationic antimicrobial peptide. Membrane depolarization studies revealed that CXCL10 disrupted membranes of the B. anthracis parent strain and the ΔftsX mutant, but only the parent strain underwent depolarization with truncated CXCL10. These findings suggest that CXCL10 is a bifunctional molecule that kills B. anthracis by two mechanisms. FtsE/X-dependent killing is mediated through an N-terminal portion of CXCL10 and is not reliant upon the C-terminal α-helix. The FtsE/X-independent mechanism involves membrane depolarization by CXCL10, likely because of its α-helix. These findings present a new paradigm for understanding mechanisms by which CXCL10 and related chemokines kill bacteria. IMPORTANCE Chemokines are a class of molecules known for their chemoattractant properties but more recently have been shown to possess antimicrobial activity against a wide range of Gram-positive and Gram-negative bacterial pathogens. The mechanism(s) by which these chemokines kill bacteria is not well understood, but it is generally thought to be due to the conserved amphipathic C-terminal α-helix that resembles cationic antimicrobial peptides in charge and secondary structure. Our present study indicates that the interferon-inducible, ELR(−) chemokine CXCL10 kills the Gram-positive pathogen Bacillus anthracis through multiple molecular mechanisms. One mechanism is mediated by interaction of CXCL10 with the bacterial FtsE/X complex and does not require the presence of the CXCL10 C-terminal α-helix. The second mechanism is FtsE/X receptor independent and kills through membrane disruption due to the C-terminal α-helix. This study represents a new paradigm for understanding how chemokines exert an antimicrobial effect that may prove applicable to other bacterial species.